Answer:
y = 3/4x + 3/2
x = 4/3y - 2
There are infinitely many solutions.
__________
To prove these equation are the same
multiply every quantity by 2 using the multiplication property of equality.
[ -6x + 8y = 12 ] = 2 [ -3x + 4y = 6 ]
2(-3x) + 2(4y) = 2(6) = 2(-3x) + 2(-4y) - 2(6) = -6x + 8y = 12 = -6x + 8y - 12
2(-3x) + 2(4y) - 2(6) = -6x + 8y - 12
-6x + 8y - 12 = -6x + 8y - 12
+6x -8y +12 +6x -8y + 12
(The general property of equality, what you do to one side, you must do to the other)
0 = 0 [always true]